MILK PRODUCTION MANAGEMENT - PATIL, PRAFULLAKUMAR V.; PATIL, MATSYAGANDHA K. ([S.l.] : CRC PRESS, 2020)
Milk Production Management, as the name implies, provides the information on different aspects related to Milk Production Management. The information in this book will be of practical utility for actual feeding of animals e.g. chapters on various rations, nutrient requirement tables, feeding of pregnant/lactating animals, feeding of calves, silage making, hydroponics technique, azolla production different feeds and fodders, fodder cultivation, computation of rations for dairy animals, feeding during scarcity periods etc. In this book different topics like common disease problems of dairy animals and their prevention and control, methods of selection, different breeding systems, semen collection and artificial insemination, different biotechniques used in animal husbandry, milking methods, embryo transfer technique, judging of cows and buffaloes, milk synthesis and milk secretion, record keeping at dairy farms, reproductive aspects of dairy animals etc. are also covered.The book also covers different terms related to animal husbandry. This book is written in simple understandable language with description of those concepts which are useful for actual management of animals. Note: T&F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
1. Introduction to Animal Husbandry 2. Distinguishing Characteristics of Indian and Exotic Breeds of Dairy; Animals and their Performance 3. External Body Parts of Cows and Buffaloes 4. Feed Nutrients Required by Animal Body 5. Feeding Standards 6. General Dairy Farm Practices- Identification, Dehorning, Castration, Exercising, Grooming, Weighing 7. Systems of Housing Dairy Animals and Maintenance of Hygiene and Sanitation at Dairy Farm Premises 8. Care of Animals at Calving and Feeding and Management of Calves 9. Management of Lactating and Dry Cows and Buffaloes 10. Identification Common Feeds and Fodder or Classification of Feedstuffs 11. Preparation of Rations for Adult Animals 12. Measures of Feed Energy 13. Systems of Breeding of Dairy Animals 14. Dairy Farm Records and their Maintenance 15. Common Disease Problems of Dairy Animals, their Prevention and Control 16. Digestive System of Cattle/Buffaloes 17. Male Reproductive System 18. Female Reproductive System 19.
OCLC-licensed vendor bibliographic record.
Keywords: Dairying -- Management; Dairy processing; Dairying -- Equipment and supplies; Dairy cattle -- Feeding and feeds; TECHNOLOGY / Agriculture / Animal Husbandry; SCIENCE / Life Sciences / Zoology / Mammals; SCIENCE / Life Sciences / General